Estrogen and the male hippocampus: Genetic variation in the aromatase gene predicting serum estrogen is associated with hippocampal gray matter volume in men. Issue 2 (6th August 2012) - Bayer, Janine; Rune, Gabriele; Kutsche, Kerstin; Schwarze, Ulrike; Kalisch, Raffael; Büchel, Christian; Sommer, Tobias
Abstract The neurosteroid 17‐beta estradiol (E2) plays an important role in neuronal plasticity, neurogenesis and neuroprotection of hippocampal neurons in slice cultures and the female brain. While some effects of E2 on hippocampal neurons observed in females were also seen in the male hippocampus, others seem to be specific to females. The current study aimed to further explore the effect of E2 on the male hippocampus by investigating the relationship between genetic variations in E2 synthesis and hippocampal gray matter (GM) volume. We chose a single nucleotide polymorphism (rs700158, SNP) in the gene CYP19A1 coding for the final enzyme (aromatase) in E2 synthesis. Men homozygous for the A allele of rs700518 have repeatedly been shown to have higher E2 serum levels than male carriers of the G allele. Two independent cohorts of healthy young men were genotyped for rs700518 and voxel‐based morphometry (VBM) was performed on structural magnetic resonance images to determine genotype dependent group differences. Men homozygous for the A allele of rs700518 had greater bilateral posterior hippocampal GM volumes in both cohorts. Thus, the genotype associated with higher E2 serum levels was also associated with greater hippocampal gray matter. © 2012 Wiley Periodicals, Inc.